Changes in hand hygiene compliance after a multimodal intervention among health-care workers from intensive care units in Southwestern Saudi Arabia - Ahmed A. Mahfouz; Ibrahim A. Al-Zaydani; Ali O. Abdelaziz; Mohammad N. El-Gamal; Abdullah M. Assiri (Springer, 2019)
The aim of this study is to measure the degree of compliance with hand hygiene practices among health-care workers (HCWs) in intensive care facilities in Aseer Central Hospital, Abha, Saudi Arabia, before and after a multimodal intervention program based on WHO strategies. Data were collected by direct observation of HCWs while delivering routine care using standardized WHO method: "Five moments for hand hygiene approach". Observations were conducted before (February-April 2011) and after (February-April 2013) the intervention by well-trained, infection-control practitioners during their routine visits. The study included 1182 opportunities (observations) collected before and 2212 opportunities collected after the intervention. The overall, hand hygiene compliance increased significantly from 60.8% (95% CI: 57.9-63.6%) before the intervention to reach 86.4% (95% CI: 84.9-97.8%) post-intervention (P = 0.001). The same trend was observed in different intensive care facilities. In logistic regression analyses, HCWs were significantly more compliant (aOR = 3.2, 95% CI: 2.6-3.8) after the intervention. Similarly, being a nurse and events after patient contact were significant determinants of compliance. It is important to provide sustained intensified training programs to help embed efficient and effective hand hygiene into all elements of care delivery. New approaches like accountability, motivation and sanctions are needed.